Explaining intention to use mobile banking: integrating perceived risk and trust into the technology acceptance model. (27th January 2021) - Van, Ha Nguyen; Pham, Long; Williamson, Stan; Chan, Ching-Yuen; Thang, Tran Duc; Nam, Vu Xuan
This study explores customers' mobile banking acceptance behaviour using the technology acceptance model (TAM) integrated with the variables of perceived risk and trust. Research employed a sample of 403 customers of one of the largest joint stock commercial banks in Vietnam. Results show that the integrated model explains more than 76% of the variability of intention to use mobile banking. The results also show that perceived risk is negatively related to trust, perceived usefulness and intention to use mobile banking. Trust is positively associated with perceived ease of use, perceived usefulness and intention to use mobile banking. Perceived ease of use is positively associated with perceived usefulness and intention to use mobile banking. Perceived usefulness is positively related to intention to use mobile banking. Implications are drawn to enhance intention to use mobile banking.